Antibiotic resistance in animals - Barton, Mary D; Pratt, Rachael; Hart, Wendy S (Communicable Diseases Intelligence, 2003)
There is currently no systematic surveillance or monitoring of antibiotic resistance in Australian animals. Registration of antibiotics for use in animals is tightly controlled and has been very conservative. Fluoroquinolones have not been registered for use in food producing animals and other products have been removed from the market because of human health concerns. In the late 1970s, the Animal Health Committee coordinated a survey of resistance in Salmonella and Escherichia coli isolates from cattle, pigs and poultry and in bovine Staphylococcus aureus. Some additional information is available from published case reports. In samples collected prior to the withdrawal of avoparcin from the market, no vancomycin resistant Enterococcus faecium or Enterococcus faecalis were detected in samples collected from pigs, whereas some vanA enterococci, including E. faecium and E. faecalis, were found in chickens. No vanB enterococci were detected in either species. Virginiamycin resistance was common in both pig and poultry isolates. Multiple resistance was common in E. coli and salmonellae isolates. No fluoroquinolone resistance was found in salmonellae, E. coli or Campylobacter. ß-lactamase production is common in isolates from bovine mastitis, but no methicillin resistance has been detected. However, methicillin resistance has been reported in canine isolates of Staphylococcus intermedius and extended spectrum ß-lactamase producing E. coli has been found in dogs. Commun Dis Intell 2003;27 Suppl:S121-S126.